2005
DOI: 10.14214/sf.371
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of riparian buffer zones to reduce sediment concentrations in discharge from peatlands drained for forestry

Abstract: In 1995-2001, the efficiency of riparian buffer zone areas to reduce the concentrations of suspended solids in discharge from peatlands drained for forestry purposes was studied at 7 locations in south-central Finland. The two largest buffer zones reduced the concentrations of suspended solids by > 70%. The efficiency of the three medium-sized buffer zones to reduce through-flow sediment concentrations was 50-60%, but no reduction occurred at the smallest two buffer areas. Thus, the capacity of buffer zones to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…This may be true for upland buffers, but other factors than width are also important. Riparian buffers can be effective in reducing nutrients even in rather narrow states (Schoonover et al 2005, McKergow et al 2006 but their efficiency increases with width, forest cover, and longitudinal continuity (Scarsbrook and Halliday 1999, Nieminen et al 2005, Harding et al 2006). Verhoeven et al (2006) reviewed measurements from different regions around the world and concluded that 2-7% of the catchment area needs to be wetland habitat in order to provide efficient water quality improvement.…”
Section: Reduction and Deceleration Of Polluted Surface Runoffmentioning
confidence: 99%
“…This may be true for upland buffers, but other factors than width are also important. Riparian buffers can be effective in reducing nutrients even in rather narrow states (Schoonover et al 2005, McKergow et al 2006 but their efficiency increases with width, forest cover, and longitudinal continuity (Scarsbrook and Halliday 1999, Nieminen et al 2005, Harding et al 2006). Verhoeven et al (2006) reviewed measurements from different regions around the world and concluded that 2-7% of the catchment area needs to be wetland habitat in order to provide efficient water quality improvement.…”
Section: Reduction and Deceleration Of Polluted Surface Runoffmentioning
confidence: 99%
“…In Finland, the area of undrained spruce swamp forests in south-and mid-boreal vegetation zones has declined by 73% since 1950s, from 1 200 000 to 300 000 hectares (Kaakinen et al 2008), and they are consequently classified as threatened habitats (Kaakinen et al 2008(Kaakinen et al , 2012. Undrained spruce swamp forests sustain high biodiversity (Hörnberg et al 1998), store carbon, and filter catchment waters before they enter the watercourses (Nieminen et al 2005b). Due to degradation by drainage, these services are lost.…”
Section: Introductionmentioning
confidence: 99%
“…If rewetting ceases the high CO2 emissions from old peat measured in drained sites (Ojanen et al 2013), significant carbon benefits are expected -but only if the decreased CO2 emissions are not counteracted by increased CH4 emissions from the blocked ditches and other new wet habitats (Cooper et al 2014, Koskinen et al 2012. Spruce swamp forests rewetted as buffer zones for runoff waters have functioned as efficient sinks for dissolved organic matter (Nieminen et al 2005b) and, after more than six years after rewetting, for phosphorus (Väänänen et al 2008) and nitrogen (Vikman et al 2010). During the first (seven) years after rewetting though, rewetting of spruce swamp forest may increase leaching of phosphorus, nitrogen and total organic carbon (Nieminen et al 2005a, Koskinen et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines list sedimentation ponds and pits, peak 46 runoff control (PRC), breaks in cleaning, submerged weirs, and wetland buffers as structures for 47 D r a f t 4 68% (Kløve 2000) and -379-85% (Samson-Dô 2015). Among structures aiming to retain SS, wetland 57 buffers have been acknowledged as highly efficient (Sallantaus et al 1998, Nieminen et al 2005. 58 However, buffer construction is restricted to areas, where sloping land enables high water table only in 59 the buffer itself, without raising water table and disturbing tree growth upstream.…”
mentioning
confidence: 99%